Hydrothermal index and entropy generation of a heated cylinder placed between two oppositely rotating cylinders in a vented cavity. (1st July 2021) - Hamzah, Hudhaifa; Canpolat, Cetin; Jasim, Laith M.; Sahin, Besir
Highlights: Mixed convection in a vented cavity having a heated cylinder is simulated. Two counter-rotating cylinders are used as an active technique to enhance heat transfer. The effect of the position and rotating speed of these cylinders on the hydrothermal index and entropy generation are detailed. The optimal thermal performance criterion is achieved at a low Reynolds number. Abstract: In this work, hydrothermal behavior and entropy generation of a heated cylinder placed between two oppositely rotating cylinders inside a vented cavity is studied numerically using the finite volume technique. The mixed convection of a steady, 2D, and laminar flow is considered for the flow through the vented cavity. For counter-rotating cylinders, according to the center of the heated cylinder, two different vertical distances, Zy and three different horizontal distances, Zx are investigated with angular rotational speeds, Ω ranging from 0 to 15. The influence of relevant parameters on hydrothermal behavior, such as Reynolds number (100 ≤ Re ≤ 500) and Grashof number (10 3 ≤ Gr ≤ 10 6 ) is taken into account throughout the simulations. The numerical results are exposed in terms of various qualitative and quantitative figures. Regardless of the position of counter-rotating cylinders, results show that the optimal thermal performance criterion, ξ is achieved at low Reynolds number ( Re =100) over the ranges of angular rotational speeds, Ω. Graphical abstract: Image, graphical abstract